P094 Impacts of 5-aminosalicylic acid on the intestinal microbiota leading to the anti-inflammatory effect. (30th January 2023) - Wada, H; Miyoshi, J; Kuronuma, S; Hibi, N; Nishinarita, Y; Oguri, N; Matsuura, M; Takeuchi, O; Kobayashi, T; Akimoto, Y; Hibi, T; Hisamatsu, T
Abstract: Background: 5-aminosalicylic acid (5-ASA) is widely used for the treatment of inflammatory bowel disease (IBD), while its anti-inflammatory mechanisms remain controversial. The intestinal microbiota plays a certain role in the pathogenesis of IBD. We hypothesised that 5-ASA exerts anti-inflammatory effects by altering the gut microbiota. Elucidating the effects of 5-ASA on gut microbiota and its contribution to anti-inflammatory effects can lead to the development of effective and economical IBD medications. Methods: Specific-pathogen-free (SPF) mice were orally administered 5-ASA for 4 weeks. The fecal bacterial compositions were examined with 16S rRNA gene amplicon sequencing analysis in mice of the 5-ASA-treatment group (5-ASA group) and no-treatment group (NT group). The immune profiles of the colonic mucosa were assessed. The feces from female mice in both groups were gavaged into germ-free (GF) female mice in separated isolators. In each isolator, these female mice (5-ASA dams and NT dams) were mated with GF male mice. The populations of CD4 + T cells in mesenteric lymph nodes (MLN) and colonic mucosal immune profiles were analysed in their pups. The pups were used for the dextran sulfate sodium (DSS)-induced colitis model to evaluate the anti-inflammatory effects of the gut microbiota altered by 5-ASA. Results: The fecal bacterial compositions changed with 5-ASA treatment over time in SPF mice. At the genus level, the relative abundance of Allobaculum increased significantly in the females of the 5-ASA group compared to the NT group (corrected p < 0.05). The same tendency was observed in male counterparts. The mRNA expression of IL-10 and IL-22 in the colonic mucosa increased significantly in mice of the 5-ASA group compared to their counterparts ( p < 0.05 in both sexes). In each isolator, the fecal bacterial compositions were similar between the dams and pups, suggesting that the gut microbiota was vertically transmitted from the dams to the pups in each group. CD4 + RORgt + T cells increased in MLN in the pups of 5-ASA dams compared to those of NT dams ( p < 0.01). The mRNA expression of TGF-b, claudin-2 and claudin-3 in the colonic mucosa increased significantly ( p < 0.001). The colonic inflammation induced by DSS was milder in 5-ASA pups compared to NT pups (Figure 1). Conclusion: Orally-administered 5-ASA altered the intestinal microbiota affecting the host immune system and leading to less susceptibility to DSS-induced colitis. Alteration of gut microbiota could be a part of the anti-inflammatory mechanisms of 5-ASA.